Shunt active power filter with modified synchronous reference frame technique and fuzzy logic current controller for harmonic mitigation - Suleiman, Musa (2017)
Harmonics is a power quality problem which represents a steady-state problem. It leads to a number of issues, ranges from equipment mal-function, which result to overheating of rotating machinery and random tripping of relays for protection of devices. Shunt active power filter (SAPF) has been the most popular choice to address harmonic disturbances in power system networks.